PERSEPSI SISWA TENTANG KEMAMPUAN GURU DALAM MENGELOLA KELAS DAN MOTIVASI BELAJAR SISWA - Lusi Gustiana (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2018)
Teachers are required to be able to manage the class with good way. If the class has good managed, it is expected that students' learning motivation will be increased. The purpose of this study  are to describes: 1) students' perceptions of the teacher's ability in class management at MTs Nurul Falah Airmolek, Subdistrict of Pasir Penyu, Indragiri Hulu Regency ?; 2) learning motivation of eighth grade students at MTs Nurul Falah Airmolek, Subdistrict of Pasir Penyu, Indragiri Hulu Regency ?; and 3) the relationship between students' perceptions of the teacher's ability in class management and learning motivation of eighth grade students of MTs Nurul Falah Airmolek, Subdistrict of Pasir Penyu, Indragiri Hulu Regency? This research was a correlation study, which connected the students' perceptions of the teacher's ability in class management and learning motivation of eighth grade students at MTs Nurul Falah Airmolek. The population in this study were all students of class VIII MTs Nurul Falah, there were 95 as the sample. Meanwhile, the population is not more than 100 people. Thus, the instrument used to collect data in this study is a questionnaire. The questionnaire has been tried out first to find the validity and reliability test. To determine the relationship between students' perceptions of the teacher's ability in class management and student learning motivation, the data was analyzed through contingency coefficient correlation techniques because the data produced are not normally distributed and not linear. The findings of this study showed that: 1) students' perceptions of the teacher's ability in class management at MTs Nurul Falah Airmolek, Pasir Penyu Subdistrict, Indragiri Hulu District, are mostly classified as medium; 2) learning motivation of eighth grade students at MTs Nurul Falah Airmolek, Pasir Penyu Subdistrict, Indragiri Hulu Regency, is mostly classified as medium; and 3) there is a relationship between students' perceptions of the teacher's ability to manage classes and learning motivation of eighth grade students at MTs Nurul Falah Airmolek, Pasir Penyu District, Indragiri Hulu Regency.